RELATIONSHIP BETWEEN INDICATORS OF MOTOR ACTIVITY AND PHYSICAL WORKABILITY OF PRIMARY SCHOOL STUDENTS - Kadutskaya, L.A.; Nikolaeva, E.S.; Viziryakin, M.N.; Soloveychenko, E.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the relationship between indicators of motor activity and physical performance of primary school students. Methods and structure of the study. The experiment involved 60 primary school students in Belgorod and the Belgorod region. In the course of the study, the physical performance of primary school students was determined according to the one-stage step test PWC170 and the value of the pulse debt accumulation index (PDI). The shagometry method consisted in counting the number of movements of primary school students during the day. To obtain objective data on the average daily volume of physical activity of students, fitness bracelets with a pedometer function were used. To determine the presence or absence of a linear relationship between the indicators of motor activity and physical performance of primary school students, the method of parametric statistics was used - the Pearson correlation coefficient. Results and conclusions. The results of the correlation analysis made it possible to state the absence of influence on the improvement of the indicators of physical performance of younger schoolchildren only by the volume of physical activity. The solution to this problem is possible by changing the nature and intensity of physical activity of students during organized at school during the school day and independent physical education classes.